(untitled) (Journal of Science and Technology Research, 2026)
Coastal areas of Bangladesh are being affected by climate change over the past four decades, and has become an escalating and notable issue in recent time. At the same time, the problem of soil salinity poses a considerable obstacle to crop production in the coastal regions of Bangladesh. Subsequently, conducting a soil salinity assessment is crucial for effective land use planning in agricultural crop production. Therefore, the aim of this research is to employ satellite remote sensing data to map soil salinity. For this study, observed electrical conductivity (EC) data are collected from SRDI, Khulna and four soil salinity (SI) indices are extracted using Landsat 8 Operational Land Imager (OLI) data from USGS Earth Explorer. According to the observed EC data, the maximum and minimum values represent the month of May 2023 and October 2022 respectively for all of the sites. The correlation coefficient between the observed EC and satellite-derived indices is more than 61% for maximum cases. Also, correlation coefficients fit better for Jalma and Batiaghata unions. The remote sensing indices have shown better performance in our present study. It can be inferred that the utilized soil salinity indices effectively identified the levels of soil salinity for this study. J. of Sci. and Tech. Res. 6(2): 43-53, 2025